O ensino de física no estado de São Paulo: os cadernos do professor e do aluno no discurso oficial e nas representações dos professores - Carvalho, Adriano Vieira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research, about the teaching of Physics in São Paulo, Brazil, starts from a contextualized view of the situation generated by the methodological changes introduced in São Paulo State public schools, with the implementation of a new Teacher's and Student's Notebooks in 2008. We understand that these notebooks are one of the manifestations of education policies advocateb by international development agencies, interested in meeting the needs and interests of Capitalism in a globalized econonomy situation (Neoliberal). We investigated how was the notebooks, as well the repercutions of it in the physics teaching practice. The research also studied the similarity of the mentioned notebooks and handout teaching systems, the motivations that led to these changes in the state public education, their relations with the policies advocated by international development agencies and the influence of civil society groups on São Paulo's educational policies. Through the use of notions of French Discourse Analysis (mainly based on the studies of E. Orlandi and M. Pêcheaux), we examined official documents of the São Paulo State Education Department (SEE-SP) and conducted interviews with in service-public high schools physics teachers. Data collected allowed us to identify discrepancies between the official discourse to the implementation of the notebooks and the representations of the physics teachers interviewed. The analysis regarding the mentioned notebooks and the educational documents and interviews taken, indicated that the implementation of such educational material presented characteristics of a techinical and instrumental teaching perspective, favoring the reduction of teachers autonomy, ignoring their experiential knownledge, trying to homogenize the teaching of physics throughout the state of São Paulo. The study concludes that the Teacher's and Student's Notebooks stand for as one the consequences of the neoliberal education policies...

Esta tese sobre o ensino de Física no estado de São Paulo, Brasil, parte de uma perspectiva contextualizada da situação gerada pela alteração metodológica insitutuída no âmbito das escolas públicas estaduais paulistas, com a implantação dos Cadernos do Professor e dos Cadernos do Aluno, em 2008, como apoio à implantação da Proposta Curricular estadual (atual currículo do Estado de São Paulo). Entendemos que esses Cadernos são uma das formas de manifestação das políticas educacionais defendidas por agências internacionais de fomento, interessadas em atender às necessidades e interesses do Capitalismo em uma situação de economia globalizada (Neoliberal). Investigamos como se deu o processo de implantação do uso dos Cadernos do Professor e do Aluno na disciplina de Física e quais as repercussões sobre a prática docente até o momento atual. A pesquisa também estudou a semelhança entre os mencionados Cadernos e os Sistemas Apostilados de Ensino, as motivações que levaram a essas modificações na educação pública paulista, as relações destas com as políticas preconizadas por agências internacionais de fomento e a influência de grupos da sociedade civil sobre as políticas educacionais paulistas. Por meio do uso de noções da Análise do Discurso de linha francesa pechetiana (baseada principalmente nos trabalhos de E. Orlandi e M. Pêcheux), examinamos documentos oficiais da Secretaria da Educação do Estado de São Paulo (SEE-SP) e realizamos entrevistas com professores da disciplina de Física em efetivo exercício na rede pública estadual paulista. Isso permitiu identificar divergências entre o discurso oficial para a implementação dos Cadernos e as representações dos professores de Física entrevistados. As análises efetuadas com relação aos mencionados Cadernos, aos documentos educacionais e às entrevistas, indicaram que o processo de implementação desse material didático apresentou...
Keywords: Ensino; Fisica; Curriculos; Apostilas; Material didático; Análise do discurso; Teaching